ROOTED NARRATIVES: A TRADITIONAL GLIMPSE INTO THE FEMALE NARRATOR'S TRAITS IN ZURINAH HASSAN’S SHORT STORY ‘ANITA’ - Nurhafizah binti Ali; Aida Mustapha; Nor Zaitolakma Abdul Samad; Mazni Muslim (Journal of Islamic, Social, Economics and Development, 2024)
This paper is a feminist reading of Zurinah Hassan's short story "Anita," with a specific emphasis on the portrayal of a traditional female character in the story. This study examines the attributes of the female narrator ‘I’, who faces constraints imposed by traditional norms and societal bias. The results of the study indicate that the female narrator is culturally compliant, dependent, passive, submissive, and lacks leadership abilities. Regardless, she experiences lesser conflicting issues with the society especially with those of the opposite gender because of her restrained and compliant demeanour.